The effect of aromatherapy by essential oil of orange on anxiety during labor: A randomized clinical trial - Fahimeh Rashidi-Fakari; Mahbubeh Tabatabaeichehr; Hamed Mortazavi (Wolters Kluwer Medknow Publications, 2015)
Background: Labor is a stressful situation that may have an adverse impact. Aromatherapy is a method to control anxiety and stress of women. This study was conducted to investigate the effect of aromatherapy using essential oil of orange on women's anxiety during labor. Materials and Methods: In this clinical trial study, 100 women during labor were randomly assigned to two groups: intervention group and control group. The women in the intervention group were exposed to orange essential oil, but the women in the control group were exposed to distilled water. The women's anxiety was assessed using the Spielberger inventory. Moreover, physiological parameters such as systolic and diastolic blood pressure, respiration and pulse rates were assessed in all the women before and 20 min after the intervention. The data were analyzed by Chi-square, Wilcoxon, paired t-test, and Mann-Whitney U test. Data were evaluated with the SPSS 16 program. The significance level of P < 0.05 was considered. Results: The level of anxiety of women in both intervention (P = 0.03) and control (P = 0.003) groups reduced after the intervention. However, the reduction was more in the intervention group (difference in anxiety scores after the intervention in comparison to before intervention = −3.08) in comparison to the control group (score = −1.14). No significant change was found in the physiological parameters of women in the intervention group after the intervention. Conclusions: Aromatherapy is a noninvasive and effective method to help women overcome their anxiety during labor. Orange scent can be useful in childbirth units to help women who are experiencing stress in labor.